Designing and Simulation of Surrounding Supporting Multicast Routing Protocol - Shaik Mahaboob Jani; Syed Umar; P.V.R.D Prasada Rao; Sridevi Gutta (Institute of Advanced Engineering and Science, 2016)
In the Wireless sensor networks having of multi-hop transmission in the Adhoc networks. These Adhoc networks having advantages of limited bandwidth and mobility which is more useful for the changing of and usage of various protocols, so that these Adhoc networks having energy conservation, simple to construct, robustness. In this paper we are proposing a new protocol called Surrounding supporting multicast routing protocol [SSMRP]. This protocol uses the mesh networks to enhance the resilience against change of node. This SSMRP utilizes the node locality which reduces the overhead of the route maintenance and it also reduces the route for good data transmissions. In this paper we clearly explain how the data will be delivered efficiently by reducing the overheads.